TECHNOLOGICAL ASPECTS OF MANUFACTURING THE FIRST KAZAKHSTAN SEASONAL INFLUENZA SPLIT VACCINE - Assanzhanova , N.N.; Kydyrbayev , Zh.K.; Ryskeldinova , Sh.Zh.; Kassenov , M.M.; Khairullin , B.M.; Tabynov , K.K. (Eurasian Journal of Applied Biotechnology, 2016)
The development of the technological stages of manufacturing an experimental, inactivated seasonal trivalent influenza split vaccine in the Republic of Kazakhstan is presented here. Master and working seed lots of the A/NIBRG-121хр (H1N1), A/NYMC X-217 (H3N2), and B/NYMC BX-49 (type B) strains were obtained for manufacturing a seasonal influenza vaccine. The purification and concentration of the three influenza virus strains were optimised and achieved by flow-through centrifugation on a linear sucrose gradient (0-60%). The optimal modes of inactivation were achieved using β-propiolactone at a final concentration of 0.1% and the subsequent splitting was carried out using the detergents Triton X-100 and Tween-80. The purified and inactivated virus concentrates were subjected to technological quality control at each production stage, as well as to stability testing. Quality control was carried out in accordance with regulations approved by the biological industry for the production and vaccines control for health care. For the first time in the Republic of Kazakhstan, a pilot batch of seasonal trivalent influenza split vaccine was produced from the NIBRG-121xp, A/NYMC X-217 (H3N2), and B/NYMC BX-49 strains. Quality-control results demonstrated that the prepared batch of vaccine meets National Pharmacopeia of Republic of Kazakhstan and European Pharmacopeia requirements and is suitable for further clinical trials.